Patient Perceptions and Interest in Robotic-Assisted Total Joint Arthroplasty - Jerry Chang, BS; Christine Wu, MD; Zoe Hinton, MD; Sean Ryan, MD; William Jiranek, MD; Michael Bolognesi, MD; Thorsten Seyler, MD, PhD (Arthroplasty Today, 2024)
Background: Robotic-assisted total joint arthroplasty (rTJA) has growing interest among patients and surgeons. However, patient interest in and perceptions of rTJA have not been well explored. We sought to investigate the influence of patient demographics on interest in rTJA and patient perceptions regarding rTJA. Methods: Patients presenting for their initial adult reconstruction consultation received an optional anonymous survey prior to seeing the provider. Patient sociodemographic parameters were recorded. Additional questions assessed interest in and perceptions surrounding rTJA. Results were analyzed to determine whether patient factors correlated with survey responses. Results: A total of 360 patients participated. Analysis of responses revealed 77.8% of patients were interested in rTJA. Interest level positively correlated with patient age (Rs = 0.139, P = .010), education level (Rs = 0.168, P = .002), household income (Rs = 0.274, P < .001), and White race (F = 4.157, P = .016). At least 100 patients believed rTJA was easier and more accurate, but more expensive and had a significant learning curve for the surgeon. Over 100 patients believed robots were capable of independently performing most or all of the rTJA operation. Conclusions: Patient interest in rTJA varies between patients. Many patients have an incomplete understanding of rTJA, and orthopaedic surgeons should address patient perceptions during surgical consultation. Level of Evidence: IV, Cross-sectional study.